Auditing versus monitoring and the role of commitment - Peter-J. Jost (Review of Accounting Studies, 2021)
This paper studies the effect of timing and commitment of verification in a principal-agent relationship with moral hazard. To acquire additional information about the agent's behavior, the principal possesses a costly technology that produces a noisy signal about the agent's effort choice. The precision of this signal is affected by the principal's verification effort. Two verification procedures are discussed: monitoring where the principal verifies the agent's behavior simultaneously with his effort choice and auditing where the principal can condition her verification effort on the realized outcome. As it is well known, the principal prefers to audit the agent's behavior if she can commit to her verification effort at the time of contracting. The main contribution of this paper is to highlight the importance of commitment by the principal to her verification effort. In particular, I show that, when the principal cannot commit to her verification effort ex-ante, the principal strictly prefers monitoring to auditing if the gains from choosing high effort are sufficiently high.
Keywords: D82; D86; M42; M52; 650; Monitoring; Auditing; Commitment; Double moral hazard